Pelatihan Pembuatan Masker Sebagai Upaya Antisipasi Penyebaran Covid-19 di Desa Anyar Kabupaten Lombok Utara - Armiani, Sucika; Fajri, Siti Rabiatul; Sukri, Akhmad; Pidiawati, Baiq Yulia (Jurnal Pengabdian UNDIKMA, 2020)
The Covid 19 pandemic is a serious problem that must be dealt with immediately. The use of masks is an effort to minimize transmission of viruses between humans. The high demand for masks, especially medical masks, is causing scarcity in the market. Therefore, cloth masks are needed as an alternative for the community to be used daily in the midst of activities facing health crises that occur. The purpose of this community service activity is to transfer sewing skills to the Anyar Village LPM partners who are members of the "Independent Beginner Group" while supporting the efforts of the village change program in producing 1000 pcs masks for the community. The implementation of the activities carried out for 2 weeks includes a site survey, problem analysis, discussion of determining the schedule of activities with the village and partners, socialization of activities to the target target, core activities include opening, training, mentoring and product delivery. The success of this activity was measured from the creation of the participant's skills so that the target of making 1000 masks was achieved. The response of partners to this activity was very well marked by the enthusiasm of the participants ie 100% attendance of participants arrived on time until the activity ended. The community service activity ended with handing over 1000 pcs of masks to the Head of Anyar Village to be distributed to the community.